Brasil y Honduras: un estudio de las relaciones bilaterales en perspectiva histórica (1906-2008) - Domínguez Ávila, Carlos Federico (2016)
The paper explores the evolution of the bilateral relations between Brazil and Honduras after a century. It is observed that the bilateral relationship generally was positive and constructive, however modest. The democratization of both countries and the current affinities between the governments suggest a moderate optimism for the future. The text use primary sources from the Arquivo Histórico do Ministério das Relacóes Exteriores (AHMRE).